2015
DOI: 10.1155/2015/343527
|View full text |Cite
|
Sign up to set email alerts
|

Correlations between Perceived Oral Malodor Levels and Self-Reported Oral Complaints

Abstract: Objectives. Even though objective data indicating the absence of oral malodor are presented to patients, they may be skeptical about the results, possibly due to the presence of some discomfort in the oral cavity. The objective of this study was to investigate whether there is an association among self-perceptions of oral malodor, oral complaints, and the actual oral malodor test result. Materials and Methods. Questions concerning self-perceptions of oral malodor and subjective intraoral symptoms were extracte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…In the present study, heavy smoking was negatively associated with the concordance between mouth odor perception and OLT evaluation. It is possible that an unpleasant intraoral taste can lead to poor subjective perceptions about bad breath [67].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, heavy smoking was negatively associated with the concordance between mouth odor perception and OLT evaluation. It is possible that an unpleasant intraoral taste can lead to poor subjective perceptions about bad breath [67].…”
Section: Discussionmentioning
confidence: 99%
“…36 Other studies have found connections between halitosis and tongue coating, strange intraoral taste, irregular dental visits, and deficient knowledge regarding halitosis management. 19 , 41 , 42 Among the elderly, self-reported halitosis was linked to subjective oral dryness, tongue coating, inadequate oral hygiene practice, and the presence of dentures. 37 …”
Section: Discussionmentioning
confidence: 99%
“…Chewing ability was calculated using a Gluco Sensor GS-II (GC, Tokyo, Japan) in accordance with the instructions from the manufacturer. Oral malodor was objectively evaluated using OralChroma (FIS, Itami, Japan) as previously described [ 18 ]. The salivary test was performed using Sill-Ha (Arkray Inc., Kyoto, Japan) in accordance with the instructions from the manufacturer.…”
Section: Methodsmentioning
confidence: 99%